Natural gas in Cyprus: The need for consolidated planning. (August 2017) - Taliotis, Constantinos; Rogner, Holger; Ressl, Stephan; Howells, Mark; Gardumi, Francesco
Abstract: The electricity supply system of Cyprus is currently dominated by oil-fired generation, with small but increasing contributions from renewable energy technologies. As regulations regarding emissions of greenhouse gases and air pollutants will become stricter with the turn of the decade, change is imminent. Available offshore gas reserves and the possibility of natural gas imports have shown that the substitution of oil with gas can reasonably be expected in the not-so-distant future. However, the framework under which change could occur has not yet been established. Should imports of gas serve as a short-term bridge until domestic gas becomes available? What are the infrastructure implications associated with such a medium-term solution? How does a policy-driven transition to gas affect energy security and how compatible is this with a liberalized electricity market? Can short- and longer term strategies be consistently designed and implemented? A cost-optimization model (OSeMOSYS), representing the electricity system of the island, is used to provide insights to these questions. Results regarding generation mix, capacity and system costs are presented for a set of scenarios. In all cases investigated, compliance with environmental regulations of the European Union after 2020 makes gas the strategic fuel of choice for low cost electricity generation. Highlights: Introduction of natural gas in electricity will reduce generation costs in Cyprus. Without natural gas, renewable energy increases but CO2 emissions increase as well. Natural gas consumption varies across time, introducing difficulties in planning. Security of supply is affected by the choice of LNG versus pipeline gas.